Color-tunable luminescence and energy transfer of Eu2+/Mn2+ co-doped Sr9Lu(PO4)7 phosphors for white LEDs. (15th February 2018) - Cui, Jian; Wang, Lei; Shi, Qiufeng; Tian, Yue; Huang, Ping; Cui, Cai'e
Graphical abstract: A series of Eu 2+ and Mn 2+ activated novel Sr9 Lu(PO4 )7 phosphors were synthesized by a solid-state reaction. Upon excitation at 365 nm, the Sr9 Lu(PO4 )7 :Eu 2+ sample can be excited efficiently, like near UV chips, and shows a strong yellowish-green color in the range 400–750 nm, peaking at 530 nm. While for the Eu 2+ and Mn 2+ ion co-doped phosphors, Sr9 Lu(PO4 )7 :Eu 2+, Mn 2+, tunable colors from yellowish-green to yellow can be obtained by varying the content of the Mn 2+ ion. Abstract: A series of Eu 2+ and Mn 2+ activated novel Sr9 Lu(PO4 )7 phosphors has been prepared through a high temperature solid state reaction. The obtained samples show a strong excitation band between 250 and 450 nm, which is in good agreement with near-ultraviolet (NUV) LED chips. Upon excitation at 365 nm, the Sr9 Lu(PO4 )7 :Eu 2+ phosphor exhibits a broad yellowish-green emission band which peaks at 530 nm. In the Eu 2+ and Mn 2+ ions co-doped phosphors Sr9 Lu(PO4 )7 :Eu 2+, Mn 2+, tunable colors from yellowish-green to yellow can be obtained by varying the content of the Mn 2+ ion. Additionally, energy transfer from the Eu 2+ to Mn 2+ ions is proven to follow a dipole–quadrupole mechanism according to the decay curves. These results indicate that the Sr9 Lu(PO4 )7 :Eu 2+, Mn 2+ phosphors could applicable for NUV based white light-emitting diodes.